Stalinism Revisited The Establishment of Communist Regimes in East-Central Europe - Tismaneanu, Vladimir (Central European University Press, 2009)
This book is a comparative framework for interpreting the relationship between late Stalinism and the communist takeovers in former Eastern Europe. A bonus for the volume is that it also provides detailed, sectorial analyses for the Romanian case, something that the field particularly lacks. The structure of the volume provides grounds for both reinterpretation and an input of fresh insights and research on the nature, dynamics, and consequences of Stalinism in Eastern and Central Europe. It contains three types of contributions: (a) general analyses of phenomena associated with the category of Stalinism; (b) case studies focusing upon aspects of establishment of communist regimes in each of the Eastern European countries; (c) historiographical evaluations of the literature dealing with the targeted period of time.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Political Science / Political Ideologies / Communism, Post-communism & Socialism; Political science; Electronic books